An analysis of the results of the 2018 World Rowing Championships - Kleshnev, V. (BioRow, 2018)
An analysis of the results of the 2018 World Rowing Championships in Plovdiv, Bulgaria, e. g. general trend, stroke rate, racing speed distribution. Five gold medals have been won by BioRow clients: